Detección de preñez en cerdas mediante prueba hormonal de embarazo humana. - Vaca Plazarte, María de los Angeles (2022)
The study is directed at determining the pregnancy detection into pregnant sows, through a human pregnancy hormone test, by determining the β-hCG hormone units into pregnant and non-pregnant sows, establishing the β-hCG hormone ranges on days 14, 15, 16 and 17 post-inseminations, determining the cost benefit and estimating the pregnancy achieved by the test. The research was performed in the San Miguel de Salcedo parish, for the sample was sampled 24 sows, between nulliparous and multiparous for Landrace, Yorkshire, Hampshire, Criolla and Duroc breeds, all with an age, what ranges between 8 and a half months and 2 years The work for the data collection was with an interview to the owners, who promised to synchronize the sows heat and insemination for the taking samples on days 14, 15, 16 and 17 post-insemination, the sample blood taking was made 1 ml from the sow's ear marginal vein, then, it was transported the sample to the laboratory, where it had been centrifuged and analyzed. It was quantified the β-hCG hormone into blood serum with the Ichroma β-hCG laboratory test, which is for human use. The results highlight, what the test was successful, diagnosing the sows studies 83% pregnancy, corresponding to 20 pregnant sows and 4 empty sows. The early pregnancy diagnosis, since the β-hCG subunit helps with an immediate decision procedure, what can be made prior to post-insemination 21 days, this technique allows a diagnosis a pig farm and improve its reproductive rates, resulting in an efficient profitability for the pig producer.